The prediction of the success of first-year MBA candidates: One business school as a case study - Scholtz, E.M.; Pienaar, J. (South African Journal of Higher Education, 2019)
Abstract The focus of this study was to determine the best predictors of academic success of first-year MBA students. Selection criteria and variables are tested for the reliable prediction of successful completion of the first year of an MBA programme (MBAI). A longitudinal quantitative research design is followed using data of students from a South African business school, enrolled between the years 2006 and 2013. The study population consisted of a total of N=777 students enrolled on the MBA programme for this period. Numerical- and verbal cognitive ability assessments gathered as part of enrolment assessment were used and compared to MBAI examination results. Logistic regression analysis was used to determine the significance of different variables to predict MBA first-year success, defined here as the successful completion of all first-year MBA modules within the first academic year. Results indicate that cognitive ability is related to MBA first-year success. The numerical was a better predictor than the verbal cognitive assessment. Type of undergraduate education was found to play a role in MBA first-year success. Language of delivery proved to have an influence on academic performance and Younger students performed better than their older counterparts did. Determining the best predictors MBA first-year success has practical implications on selection processes and throughput.